Internal iliac artery balloon occlusion during cesarean hysterectomy in women with placenta previa accreta. Issue 1 (8th February 2019) - Chen, Meng; Lv, Bin; He, Guolin; Liu, Xinghui
Abstract: Objective: To investigate the effect of balloon occlusion of internal iliac arteries during cesarean hysterectomy in women with placenta previa accreta. Methods: Retrospective cohort study conducted using medical records of women with placenta previa and pathologically confirmed accreta taken from a single tertiary center in Chengdu, China, between January 1, 2012 and December 31, 2017. Baseline characteristics and pregnancy outcomes were compared between women with and without balloon occlusion of internal iliac arteries during cesarean delivery. The primary outcome was a composite outcome: estimated blood loss greater than or equal to 3.0 L, massive transfusion (transfusion of 10 or more units of packed red blood cells), and maternal intensive care unit admission. Results: There were 114 patients included in the study, 83 (72.8%) in the balloon group and 31 (27.2%) in the control group. Both propensity score analysis (18 [78.3%] vs 15 [65.2%], P =0.326) and multivariate logistic analysis (adjusted odds ratio 0.54, 95% confidence interval 0.20–1.45; P =0.221) showed that intraoperative balloon occlusion of internal iliac arteries was not associated with the primary outcome. Conclusion: Balloon occlusion of internal iliac arteries during cesarean hysterectomy in women with placenta previa accreta was not associated with improved maternal outcomes. Abstract : Intraoperative internal iliac artery balloon occlusion is not associated with improved outcomes for women with placenta accreta.